2022
DOI: 10.1111/ele.14026
|View full text |Cite
|
Sign up to set email alerts
|

Temporal correlations among demographic parameters are ubiquitous but highly variable across species

Abstract: Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 78 publications
3
22
0
Order By: Relevance
“…Interestingly, there is no general consensus on the degree to which positive or negative covariance in demographic parameters are more common in the wild, nor if the sign, magnitude or type of (st)age-specific demographic parameters involved correlate with the position of a species along the fast–slow continuum (but see a recent comparative study, Fay et al ., 2022). From empirical studies, positive covariances have been reported predominantly in long-lived species (e.g., Dahlgren et al ., 2016; Rotella et al ., 2012; van de Pol et al ., 2010) with substantial (e.g., Coulson et al ., 2005) or weak (e.g., Altwegg et al ., 2007; Compagnoni et al ., 2016; Johnson et al ., 2010) effects on fitness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there is no general consensus on the degree to which positive or negative covariance in demographic parameters are more common in the wild, nor if the sign, magnitude or type of (st)age-specific demographic parameters involved correlate with the position of a species along the fast–slow continuum (but see a recent comparative study, Fay et al ., 2022). From empirical studies, positive covariances have been reported predominantly in long-lived species (e.g., Dahlgren et al ., 2016; Rotella et al ., 2012; van de Pol et al ., 2010) with substantial (e.g., Coulson et al ., 2005) or weak (e.g., Altwegg et al ., 2007; Compagnoni et al ., 2016; Johnson et al ., 2010) effects on fitness.…”
Section: Discussionmentioning
confidence: 99%
“…From empirical studies, positive covariances have been reported predominantly in long-lived species (e.g., Dahlgren et al ., 2016; Rotella et al ., 2012; van de Pol et al ., 2010) with substantial (e.g., Coulson et al ., 2005) or weak (e.g., Altwegg et al ., 2007; Compagnoni et al ., 2016; Johnson et al ., 2010) effects on fitness. In contrast, negative covariances were less often detected (Fay et al ., 2022), with often small effects on ln(λ s ). To our knowledge, relatively few studies have specifically addressed this question among species towards the fast-end of the continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we test the hypothesis, proposed by Fay et al (2022), that cross-season correlations in survival and reproduction are predominately a result of environmental conditions, and thus their magnitude and direction should differ among geographically separate populations. Furthermore, we quantify the proportion of variation in realised population growth rates that is attributable to the underlying demographic correlations using a transient-LTRE.…”
Section: Introductionmentioning
confidence: 97%
“…Positive correlations increase population size fluctuations, reducing the long-term population growth rate (Tuljapurkar & Orzack 1980;Compagnoni et al 2016), with particular implications for endangered populations (Tuljapurkar & Orzack 1980;Boyce et al2006). Positive correlations among demographic rates also appear to be more common than negative correlations, particularly in iteroparous species (Yoccoz et al 2002;Fay et al 2022). Despite their potential importance as a secondary driver, correlations in demographic rates are still rarely considered in population viability analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation